Student's Enthusiasm Toward Badminton Instruction - Maldini Manda Putra; Yopi Meirizal; Hendya Alif Junanda (Journal of Physical and Outdoor Education, 2025)
Learning is a systematically designed process intended to facilitate students' acquisition of knowledge and skills. Badminton is a sport that involves the use of rackets and a shuttlecock, played either in singles or doubles format. Enthusiasm refers to a spontaneous emotional response characterized by excitement and eagerness toward a particular activity or event. This study aims to examine the level of students' enthusiasm toward badminton instruction. The research employed a quantitative descriptive method. The population consisted of all eighth-grade students at SMP Negeri 47 Bandung, located in the city of Bandung. A purposive sampling technique was utilized to select a sample of 30 students. Data were collected using a questionnaire as the primary research instrument. The results of data analysis revealed the following percentages for each sub-variable: enjoyment (40.44%), interest (47.77%), attentiveness (31%), persistence in learning (16.66%), resilience in overcoming challenges (37.88%), concentration during instruction (42.55%), and independent learning (14.66%). These findings indicate that the majority of students who demonstrated enthusiasm in badminton instruction were predominantly categorized under the sub-variable Interest.